2016
DOI: 10.1038/oncsis.2016.10
|View full text |Cite
|
Sign up to set email alerts
|

The Bag-1 inhibitor, Thio-2, reverses an atypical 3D morphology driven by Bag-1L overexpression in a MCF-10A model of ductal carcinoma in situ

Abstract: Mammary MCF-10A cells seeded on reconstituted basement membrane form spherical structures with a hollow central lumen, termed acini, which are a physiologically relevant model of mammary morphogenesis. Bcl-2-associated athanogene 1 (Bag-1) is a multifunctional protein overexpressed in breast cancer and ductal carcinoma in situ. When present in the nucleus Bag-1 is predictive of clinical outcome in breast cancer. Bag-1 exists as three main isoforms, which are produced by alternative translation initiation from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…We have previously reported that Thio-2, a small molecule with a 2-arylbenzothiazole scaffold, inhibits the binding of BAG1L to the AR and the proliferation of AR-positive LNCaP cells . As Thio-2 is nonselective, we synthesized 47 derivatives with different substitutions in the benzothiazole (building block A) and aryl (building block B) moieties in an attempt to make it more selective. This generated 17 compounds of type A1B, 14 of type A2B, five of type A3B, and 11 of type A4B (Figure A and Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that Thio-2, a small molecule with a 2-arylbenzothiazole scaffold, inhibits the binding of BAG1L to the AR and the proliferation of AR-positive LNCaP cells . As Thio-2 is nonselective, we synthesized 47 derivatives with different substitutions in the benzothiazole (building block A) and aryl (building block B) moieties in an attempt to make it more selective. This generated 17 compounds of type A1B, 14 of type A2B, five of type A3B, and 11 of type A4B (Figure A and Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…To test if pharmacological interference of the BAG domain of Bag-1L would indeed impair AR action, we tested the efficacy Thio-2, a tool compound BAG domain inhibitor. Thio-2 has previously been postulated to bind to the BAG domain and to inhibit the interaction between Hsp70 and Bag-1 ( Enthammer et al, 2013 ; Papadakis et al, 2016 ). A consequence of this is the reduce growth of breast cancer cells, but so far this compound has not been tested in PCa.…”
Section: Resultsmentioning
confidence: 99%
“…This notion is supported by our findings pointing to a druggable pocket within the BAG domain of Bag-1L, which overlaps our triple mutation (CMut). An inhibitor (Thio-2) that targets the BAG domain was shown to be efficacious in blocking the antiapoptotic action of Bag-1 in breast cancer and melanoma cells ( Enthammer et al, 2013 ; Papadakis et al, 2016 ). In the present study we show that it is also effective in inhibiting the Bag-1L BAG:AR tau-5 interaction and suppressing PCa cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…In general, BAG-1 is expressed at low levels in human tissues (Takayama et al 1998), but is frequently overexpressed in invasive cancers (Papadakis et al 2016;Takayama et al 1998; Electronic supplementary material The online version of this article (doi:10.1007/s12192-016-0751-z) contains supplementary material, which is available to authorized users. et al 1999).…”
Section: Introductionmentioning
confidence: 99%